DATABASE OF MYCORRHIZAL FUNGI OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The computerized database of mycorrhizal fungi, which includes detailed information about 211 mycorrhizal species of the RA was created. The database allows for use this information for scientific and practical purposes
Keywords: mycorrhizal fungi, the database, information field